SEMANTICS OF PROBABILITY AND POSSIBILITYIN ENGLISH AND RUSSIAN LANGUAGES - Mukhamedova Nigora (Western European Studies, 2025)
This article explores the semantics of probability and possibility in English and Russian, focusing on how these two languages express degrees of certainty, likelihood, and potentiality. The study examines modal verbs, adverbs, and other lexical and grammatical markers that convey epistemic modality. Through comparative semantic analysis, the paper identifies the functional similarities and differences between English and Russian modal systems, emphasizing the cultural and cognitive underpinnings of expressing probability and possibility. Special attention is paid to the contextual usage of modals like may, might, can in English and their Russian counterparts such as может быть, возможно, наверное. The research highlights how each language systemizes uncertainty and modality, offering insights into the typological and pragmatic distinctions of expressing epistemic judgments
Keywords: Semantics of modality; Probability and possibility